Pengaruh Struktur Modal, Firm Size, Likuiditas, dan Profitabilitas terhadap Pengungkapan Corporate Social Responsibility pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Grace Angelia; Revi Arfamaini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Corporate Social Responsibility (CSR) describes a very broad concept that covers many and varied topics such as human rights, corporate governance, occupational health and safety, environmental impact, working conditions, and contributions to economic development. The objective of this study is to analyze the influence of Capital Structure, Firm Size, Liquidity, and Profitability on Corporate Social Responsibility Disclosure in Energy Sector Companies Listed on the Indonesia Stock Exchange from 2020 to 2023. Quantitative data was applied, with data sources obtained from financial reports and corporate sustainability reports. SPSS version 31 was used as the data analysis technique. The findings revealed that Capital Structure does not have an influence on Corporate Social Responsibility, with a significant value of 0.140 > 0.05. Firm Size does not influence Corporate Social Responsibility Disclosure, with a significant value of 0.062 > 0.05. Liquidity does not influence Corporate Social Responsibility Disclosure, with a significant value of 0.137 > 0.05. Furthermore, Profitability has an effect on Corporate Social Responsibility Disclosure, with a significant value of <0.001 < 0.05.